The selective catalytic reduction of NO with propene over Cu-supported Ti-Ce mixed oxide catalysts: Promotional effect of ceria - Liu, J.; Li, Xin Yong; Zhao, Q.; Zhang, D.; Ndokoye, P. (2013)
A series of Cu-supported Ti-Ce mixed oxide catalysts (Cu/Ti1-xCexO2), with x = 0, 0.1, 0.2, 0.3, 0.5, 1.0, were evaluated for selective catalytic reduction (SCR) of NO with C 3H6 under lean-burn conditions, and the promotional effect of ceria additive was investigated systematically. Among the tested catalysts, Cu/Ti0.9Ce0.1O2 exhibited excellent low-temperature activity, which achieved a maximum N2 yield of 50.3% and NOx conversion of 66.2% at 240 C. The generation of Ti-O-Ce mixed bond raised the quantity of Lewis acid sites and therefore improved the distribution of the copper oxide species on the catalyst surface. The high SCR activity of the Cu/Ti0.9Ce0.1O2 was mainly attributed to the abundant Lewis acid sites and the high ratio of adsorbed oxygen on the catalyst surface, which provided more adsorption centers for NO and promoted the NO oxidation in the SCR reaction. Furthermore, the high concentration of Cu2+ was beneficial to NO adsorption. Combined with the in situ FT-IR results, it was suggested that the synergistic effect of ceria and copper promoted the formation and reactivity of nitrates, oxygenated hydrocarbons, and key intermediates isocyanate (-NCO species), and consequently, Cu/Ti0.9Ce0.1O2 catalyst exhibited the excellent SCR performance.